Кремнієвий p–i–n-фотодіод із підвищеною імпульсною чутливістю - Kukurudziak, Mykola; Dobrovolsky, Yuriy (PE "Politekhperiodika", Book and Journal Publishers, 2021)
P-n junction semiconductor photodetectors are widely used in various fields of science and technology, including automation and telecontrol, instrumentation equipment, tracking systems, guidance, etc. The most demanded photoelectronic devices are silicon p-i-n photodiodes (PD). Their main field of application are installations using laser beams of near IR optical radiation spectrum, λ = 1060 nm, in particular.The article provides considerations and limit requirements for production of high-responsivity silicon p-i-n photodiodes and making theoretical parameters consistent with real photodiodes made according to the design. Characteristic properties of technology, construction and final parameters of the manufactured four-element segment p–i–n photodiode with a guard ring are described.The authors describe the criteria for choosing the material for making high-responsivity photodiodes. Results of the theoretical design for the capacitance of the photodiode based on the materials of different resistivity are presented. A theoretically possible value for the dark current of the responsive elements and the guard ring is considered for the silicon of 18 kOhm·cm. Criteria for the thickness of the PD crystal and the doped areas that provide for the maximum width of the space-charge region are presented. The dependence of the current pulse monochromatic responsivity from the operating voltage of the photodiode is shown for substrates with different thickness.The photodiodes obtained during this study have the pulse monochromatic responsivity of 0.48 A/W, which is higher than that of commercial products of well-known foreign manufacturers. The results achieved demonstrate that this technology is effective and the assumptions made during the calculation stage are valid.